Palliation for Inoperable Infectious and Neoplastic Long-Term Surgical Complications - Bryant, Peter A.; Shinall, Myrick C., Jr. (Clinics in Colon and Rectal Surgery, 2025)
Inoperable complications from pelvic surgery or the progression of unresectable colorectal neoplasms may create a situation requiring a focus on quality of life over cure within a palliative care framework. This review outlines management strategies for some common, incurable, long-term sequelae patients of colorectal surgeons may experience, including advanced cancer-causing obstruction, bleeding, and pain; chronic anastomotic leak after pelvic surgery, including salvage techniques; and chronic pelvic pain after surgery. Strategies include palliative operations, endoscopic and minimally invasive techniques, and unique approaches to pain control and symptom management. The paper also reviews evidence on the benefit of palliative care specialists, when such specialists may be beneficial, as well as how the colorectal surgeon may facilitate decision-making in treatment decisions of incurable disease.
Keywords: colorectal cancer; palliative care; complications; anastomotic leak